ANALYSIS OF THE IMPACT OF COVID-19 ON THE PATHEK BEACH TOURISM AREA - Muhammad Zaid Nuriyanto; Sri Astutik; Bejo Apriyanto; Elan Artono Nurdin; Muhammad Asyroful Mujib (DEPARTMENT OF GEOGRAPHY EDUCATION, UNIVERSITY OF JEMBER, 2020)
The purpose of the study was to analyze the impact of the Covid-19 pandemic on the tourist area of Pathek Beach, Gelung Village, Panaurakan District, Situbondo Regency. The method used by researchers in this study is a qualitative descriptive method. The results showed that the Pathek Beach tourist area experienced a major impact from the covid-19 pandemic. Tourist visits from this tourist area have decreased drastically by up to 50%. The economy of the community around the Pathek Beach area, especially the traders, experienced a 50-75% decline in turnover during the pandemic.